Fourier Spectrums Clustering for Automated Facies Recognition of Field Y; Через интеграцию геонаук - к постижению гармонии недр - Tengelidi D. I. Dmitry Ivanovich; Rukavishnikov V. S. Valery Sergeevich; Mityaev M. Y.; Fuks O. M. (Well Logging, 2016)
Title screen